People's Voice and Civil Society Participation as a Core Element of Universal Health Coverage Reforms: Review of Experiences in Iran - Dheepa Rajan; Mohammad Hadi Ayazi; Maziar Moradi-Lakeh; Narges Rostamigooran; Maryam Rahbari; Behzad Damari; Ali Asghar Farshad; Reza Majdzedeh; Kira Koch (Kerman University of Medical Sciences, 2022)
Health governance challenges can make or break Universal Health Coverage (UHC) reforms. One of the biggest health governance challenges is ensuring meaningful participation and adequately reflecting people's voice in health policies and implementation. Recognizing this, Iran's Health Transformation Plan (HTP) lays out the country's blueprint for UHC with an explicit emphasis on the 'socialization of health'. 'Socialization' is seen as a key means to contribute to HTP objectives, meaning the systematic and targeted engagement of the population, communities, and civil society in health sector activities. Given its specific cultural and historical context, we sought to discern what notions such as 'civil society', 'non-governmental organization', etc. mean in practice in Iran, with the aim of offering policy options for strengthening and institutionalizing public participation in health within the context of the HTP. For this, we reviewed the literature and analysed primary qualitative data. We found that it may be more useful to understand Iranian civil society through its actions, i.e. defined by its motivation and activities rather than the prevailing international development understanding of civil society as a structure which is completely independent of the state. We highlight the blurry boundaries between the different types of civil society organizations and government institutions and initiatives, as well as high levels of overlaps and fragmentation. Reducing fragmentation as a policy goal could help channel resources more efficiently towards common HTP objectives. The national health assembly model which was first launched in 2017 offers a unique platform for this coordination role, and could be leveraged accordingly.